2021
DOI: 10.3389/fnhum.2021.732648
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Gait Perturbation Training in Parkinson's Disease and Healthy Older Adults: A Systematic Review and Meta-Analysis

Abstract: Background: Gait impairments are common in healthy older adults (HOA) and people with Parkinson's disease (PwPD), especially when adaptations to the environment are required. Traditional rehabilitation programs do not typically address these adaptive gait demands in contrast to repeated gait perturbation training (RGPT). RGPT is a novel reactive form of gait training with potential for both short and long-term consolidation in HOA and PwPD. The aim of this systematic review with meta-analysis is to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…PBT has also been found to improve perturbation recovery measures ( 156 , 159 , 160 , 177 ) and some studies have reported improvements in clinical balance tests such as the Berg Balance Scale in people with Parkinson's disease ( 173 , 174 , 178 ). However, while there appears to be interest in the potential for PBT to improve a broad range of gait and balance measures in clinical populations [see reviews of Hulzinga et al ( 179 ), Coelho et al ( 180 )], as outlined in section What is task-specificity in the context of PBT? and How does PBT differ from other task-specific approaches to fall prevention?, the effects do not necessarily generalize to less-reactive balance and gait measures.…”
Section: Implementation In Practicementioning
confidence: 99%
“…PBT has also been found to improve perturbation recovery measures ( 156 , 159 , 160 , 177 ) and some studies have reported improvements in clinical balance tests such as the Berg Balance Scale in people with Parkinson's disease ( 173 , 174 , 178 ). However, while there appears to be interest in the potential for PBT to improve a broad range of gait and balance measures in clinical populations [see reviews of Hulzinga et al ( 179 ), Coelho et al ( 180 )], as outlined in section What is task-specificity in the context of PBT? and How does PBT differ from other task-specific approaches to fall prevention?, the effects do not necessarily generalize to less-reactive balance and gait measures.…”
Section: Implementation In Practicementioning
confidence: 99%
“… 21 , 50 This finding was consistent with previous reviews that demonstrated beneficial effects of PBT in fall reduction among young and older healthy adults and individuals with Parkinson’s disease, 18 , 23 , 25 and contrary to the systematic review’s result by Hulzinga et al which found a non-significant improvement in balance when comparing gait perturbation training with non-perturbation training in Parkinson’s disease and healthy older adult. 24 Although PBT showed a favorable effect in balance, 2 included studies showed a non-significant reduction in falling rates over 1-year post-training. 20 , 39 This discrepancy may result from the small sample size that leads to inability to reach sufficient statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of PBT on balance and balance confidence has not been conclusively determined. In addition, prior reviews focused mainly on the effects of PBT in young and older healthy adults and individuals with Parkinson’s disease, 18 , 23 - 25 there is no review focused on PBT in the treatment of patients with stroke. Therefore, the purpose of this systematic review and meta-analysis was to investigate the effectiveness of perturbation-based training (PBT) on balance and balance confidence in patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…PBT has also been found to improve perturbation recovery measures (Shimada et al, 2004, Bieryla and Madigan, 2011, Aviles et al, 2019, Pigman et al, 2019 and some studies have reported improvements in clinical balance tests such as the Berg Balance Scale in people with Parkinson's disease (Smania et al, 2010, Shen and Mak, 2015, Wong-Yu and Mak, 2015b). However, while there appears to be interest in the potential for PBT to improve a broad range of gait and balance measures in clinical populations (see reviews of Hulzinga et al (2021), Coelho et al (2022)), as outlined in section 2.2 and 2.3, the effects do not necessarily generalise to less-reactive balance and gait measures. To our knowledge, no current studies in clinical populations have reported non-responders in terms of adaptation of the stability recovery response to PBT.…”
Section: What Is the Evidence For Pbt In Clinical Populations?mentioning
confidence: 99%